1987
DOI: 10.1111/j.1365-2915.1987.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin and chymotrypsin‐Iike enzymes of the sandfly Phlebotomus papatasi infected with Leishmania and their possible role in vector competence

Abstract: Phlebotomus papatasi (Scopoli) is susceptible to infection with Leishmania major Yakimov & Schokov and resistant to L. donovani Laveran & Mesnil. The possibility that susceptibility depends on midgut levels of trypsin and chymotrypsin-like (esterolytic) enzymes was investigated. Infection with L. major reduced the trypsin-like activity to 93.5% and 86% of the control value at 20 and 30 h post feeding and increased it to 106% at 52 h. Infection with L. donovani reduced trypsin-like activity to 64% and 73% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 25 publications
(16 reference statements)
2
97
0
1
Order By: Relevance
“…Transformed promastigotes inside the sandfly gut have to overcome potentially lethal conditions; for example, approximately 50% of L. major ingested by Phlebotomus papatasi during initial infection died during this early stage. 7 Borovsky and Schlein 6 suggested that trypsin-like activity in the midgut of the P. papatasi prevented survival of L. donovani. Pimenta and others 7 observed that the midgut environment, in the first few hours after blood feeding, is harmful even for a strain of L. major that is capable of complete development in the sandfly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformed promastigotes inside the sandfly gut have to overcome potentially lethal conditions; for example, approximately 50% of L. major ingested by Phlebotomus papatasi during initial infection died during this early stage. 7 Borovsky and Schlein 6 suggested that trypsin-like activity in the midgut of the P. papatasi prevented survival of L. donovani. Pimenta and others 7 observed that the midgut environment, in the first few hours after blood feeding, is harmful even for a strain of L. major that is capable of complete development in the sandfly.…”
Section: Discussionmentioning
confidence: 99%
“…After the sandfly has had an infected blood meal, ingested amastigotes (non-flagellate forms) differentiate into dividing promastigotes (flagellate forms) to establish the parasite life cycle. However, there are numerous adverse conditions to overcome in the midgut of the host, including digestive enzyme activities 6 and the synthesis of a physical barrier (the peritrophic matrix; PM), 7 and the need to bind to the midgut cells 8,9 to avoid excretion. Lipophosphoglycan, the major Leishmania surface glycoconjugate, protects the parasites from the enzyme activities of its host and mediates parasite attachment to the midgut of the sandfly.…”
Section: Introductionmentioning
confidence: 99%
“…Important roles have been described for the LPG coat including protection against the hydrolytic peptidase associated with bloodmeal digestion [46], binding of the parasite to the midgut wall [47], and, in some steps, it is required for the establishment of macrophage infections and for survival in the insect vector through complementation and oxidant resistance [24,25].…”
Section: 2a Lpgmentioning
confidence: 99%
“…During its life cycle, Leishmania parasites must sur-vive under extremely adverse conditions represented by the digestive hydrolases present in the midgut, have to avoid passage with the blood meal and must digest PM in order to attach to the insect epithelium (Borovsky andSchlein 1987, Pimenta et al 1997). The recognition of receptors in the microvilli by the Leishmania lipophosphoglycan (LPG), the dominant cell surface glycoconjugate, is a crucial step for Leishmania survival, as mutants in LPG synthesis are unable to sustain infection in the sand fly (Butcher et al 1996).…”
Section: Leishmania Interaction -The Role Of Lipophosphoglycan (Lpg)mentioning
confidence: 99%